Cost Accounting: A Multidimensional Emphasis (Book). - Morris, Michael H.; Meyer, Philip E. (The Accounting Review, 1983)
Abstract Reviews the book "Cost Accounting: A Multidimensional Emphasis," by Ahmed Belkaoui.